Diversidade clínica, epidemiológica e Genética do Mycobacterium tuberculosis na região Noroeste paulista - Pedro, Heloisa da Silveira Paro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Tuberculosis is considered a high priority public health problem. There is increasing evidence that the variation in Mycobacterium tuberculosis strains play an important role in the outcome of infections by tuberculosis. Apart from describing sociodemographic, clinical, epidemiological and bacteriological aspects of tuberculosis (TB) and correlating the distribution of resistance to antituberculosis drugs, one objective of this study was to evaluate the diversity of the genotypes of M. tuberculosis isolates using the Spoligotyping (spacer oligonucleotide typing) and MIRU-VNTR (Mycobacterial Interspersed Repetitive Units variable-number tandem repeats) techniques. With respect to drug resistance, cultures of M. tuberculosis and susceptibility tests showed that strains from people previously submitted to TB treatment or infected with HIV have more resistance to drugs compared to those without these characteristics (p <0.05 ). Resistant cases are mostly pulmonary M. tuberculosis, and have positive smear test results. Molecular analysis showed that of the 377 samples, 14 MIRU-VNTR loci had complete profiles; the 10, 16, 23, 26, 27, 31, 39 and 40 loci had high discriminatory power (0.6) the 2, ETRB and Mtub21 loci were moderately discriminatory (0.3) and 4, 20 and 24 loci had low discriminatory power (0.3). Ninety-two different patterns were observed in the 250 M. tuberculosis isolates analyzed by spoligotyping and different families were identified as Haarlem (H), Latin American and Mediterranean (LAM), T Family, undesignated (U), S lineage and X Family. Significant genetic variability was observed in M. tuberculosis isolates circulating in the northwestern region of Sao Paulo State when analyzed by spoligotyping and MIRU-VNTR

A tuberculose é considerada um problema prioritário de saúde pública. Há cada vez mais evidências de que, a variação das cepas de M. tuberculosis tem um papel importante no resultado da infecção por tuberculose. No presente estudo, além de descrever os aspectos sociodemográficos, clínico-epidemiológicos e bacteriológicos da tuberculose e relacionar com a distribuição de resistência aos fármacos antituberculose, também objetivou-se avaliar a diversidade dos genótipos de isolados de Mycobacterium tuberculosis utilizando as técnicas de Spoligotipyng (Spacer Oligonucleotide Typing) e MIRU-VNTR (Mycobacterial Interspersed Repetitive Units-variable-number tandem repeats). Com relação à resistência aos fármacos, as culturas de MT e os testes de sensibilidade mostram que cepas de pessoas que fizeram tratamento de TB anterior ou infectados pelo HIV apresentaram mais resistência os fármacos quando comparados aos que não apresentavam essas características (p<0,05). Os casos resistentes, em sua maioria, são de origem pulmonar e apresentam baciloscopia positiva. A análise molecular mostrou que das 377 amostras com perfis completos para 14 loci MIRU-VNTR, os loci 10, 16, 23, 26, 27, 31, 39 e 40 tiveram um alto poder discriminatório (0.6), os loci 2, ETRB e Mtub21 foram moderadamente discriminatórios (0.3) e loci 4, 20 e 24, baixo poder discriminatório (0.3). Dos 250 isolados de M. tuberculosis analisados por spoligotyping, 92 diferentes padrões foram observados e diferentes famílias foram identificadas: Haarlem (H), Latin American and Mediterraneam (LAM), T Family, undesignated (U), S lineage e X Family. Significativa variabilidade genética foi observada nos isolados de M. tuberculosis circulantes na região Noroeste Paulista quando analisados por spoligotyping e MIRU-VNTR
Keywords: Genética; Epidemiologia molecular; Tuberculose; Mycobacterium tuberculosis